Motivation to share knowledge using wiki technology and the moderating effect of role perceptions. (28th July 2015) - Arazy, Ofer; Gellatly, Ian; Brainin, Esther; Nov, Oded
Abstract : One of the key challenges for innovation and technology‐mediated knowledge collaboration within organizational settings is motivating contributors to share their knowledge. Drawing upon self‐determination theory, we investigate 2 forms of motivation: internally driven (autonomous motivation) and externally driven (controlled motivation). Knowledge sharing could be viewed as a required in‐role activity or as discretionary extra‐role behavior. In this study, we examine the moderating effect of role perceptions on the relations between each of the two motivational constructs and knowledge sharing, paying particular attention to the affordances of the enabling information technology. An analysis of survey data from a wiki‐based organizational encyclopedia in a large, multinational firm reveals that when contributors' motivation is externally driven, they are more likely to share knowledge if this activity is viewed as in‐role behavior. However, when contributors' motivation is internally driven, they are more likely to participate in knowledge sharing when this activity is viewed as extra‐role behavior. Theoretical and practical implications are discussed.